Pred fluid system for well cementation and water plugging and preparation method thereof

By using pre-liquid systems of nano-sealing adsorbent materials, selective temporary plugging materials and interface reinforcement materials during cementing, the problem of insufficient pre-sealing of water layers in the prior art is solved, and a more efficient water layer is achieved Extend the life of sealing and oil and gas well development.

CN119463827APending Publication Date: 2025-02-18CHINA NAT PETROLEUM CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310996666.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing cementing measures have shortcomings in improving the waterproof performance of the cement slurry system. They have failed to effectively pre-seal the oil well water layer, resulting in serious problems in the later development hedging, affecting the development life of the oil and gas well.

Method used

A preliminary system for cementing water blocking is provided, including nano-sealing adsorption materials, selective temporary plugging materials and interface reinforcement materials, which are prepared by on-site mixing and stirring to form an efficient water layer pre-sealing system.

Benefits of technology

This pre-liquid system can effectively improve the quality of interface sealing of oil fields, reduce the problem of interface sealing failure caused by water flowing water invasion and ion exchange, and extend the development life of oil and gas wells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463827A_ABST
    Figure CN119463827A_ABST
Patent Text Reader

Abstract

The invention provides a prepad fluid system for well cementation and water plugging and a preparation method of the prepad fluid system. The prepad fluid system comprises the following components in parts by weight: 10-30 parts of a nano channeling sealing adsorption material, 8-20 parts of a selective temporary plugging material, 2-5 parts of an interface reinforcing material and 50-80 parts of water. The nanometer channeling sealing adsorption material is composed of silica sand and nanometer liquid silicon, and the mass ratio of the silica sand to the nanometer liquid silicon is 1: (3-4). The selective temporary plugging material is used for plugging and filling a long open hole large-section water layer, the nano plugging material remaining near the well wall is high in activity and can effectively participate in cement hydration by utilizing the pozzolanic effect of the nano plugging material and cement, the gelation transition time of cement stone near the well wall interface is shortened, and hydrated calcium silicate formed by the nano plugging material and the cement is low in sensitivity; the water-layer interface cementing agent is suitable for various formation fluids, and is matched with an interface reinforcing material, so that the interface cementing strength of a water-layer section can be effectively improved, the plugging quality of an oil-field water-layer interface is improved, and the problems of interface sealing failure and water-layer cement sealing quality caused by water-layer flowing water invasion and ion exchange are effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil and gas field cementing engineering, and specifically relates to a pre-fluid system for cementing and water plugging and a preparation method thereof, which mainly prevents the casing damage problem in later development caused by poor sealing quality of oil field water layers and improves the development life of oil and gas wells. Background Art

[0002] The water layers in the oil wells of Changqing Oilfield are abundant and have a large span. There are water layers in Luohe, Zhiluo, Yan'an and Yanchang formations, with a span of 600-800m. The water layers are active, highly heterogeneous and have a permeability of 30-400mD. The casing damage problem caused by the quality problem of cementing and sealing of the water layers in the oil wells is becoming more and more obvious. The number of casing-damaged wells and water-flooded wells is increasing year by year. The water source of the upper formations in some blocks is seriously polluted, making it impossible to explore and develop some blocks. The casing in some blocks is seriously corroded, resulting in water-flooded oil layers. The production capacity recovery effect after casing damage and well repair is not obvious, and the recovery rate is greatly reduced (the water content is basically above 90%), which seriously affects the recovery rate of the oil field.

[0003] The existing cementing measures are only designed to improve the waterproof performance of the cement slurry system, but no relevant design and research have been conducted on the pre-plugging pre-fluid system for the oil well water layer before cementing.

[0004] The application number published by the State Intellectual Property Office is 202011396918.4, and the patent name is "An interface-enhanced pre-fluid for oilfield cementing and its preparation method and application". The pre-fluid includes 100 parts by weight of tap water, 2-5 parts by weight of suspending agent, 10-50 parts by weight of activatable mineral active materials, 2-5 parts by weight of whiskers and / or fibers, and 2-5 parts by weight of penetrant. The interface-enhanced pre-fluid for oilfield cementing can improve the annular isolation capacity under complex geological conditions such as high-permeability layers and leaky layers, and improve the cementing quality, but the bonding strength is low and it does not have the water layer water blocking performance. Summary of the invention

[0005] The purpose of the present invention is to provide a pre-fluid system for cementing and water plugging, which can improve the plugging quality of the oil field water layer interface.

[0006] Another object of the present invention is to provide a method for preparing a pre-fluid system for cementing and water plugging, which can be obtained by mixing and stirring a mixed solution and a mixed solid phase on site, and is easy to prepare on site.

[0007] To this end, the technical solution provided by the present invention is as follows: A pre-fluid system for cementing and water plugging comprises the following components in parts by weight: 10-30 parts of nanometer channel blocking adsorption material, 8-20 parts of selective temporary plugging material, 2-5 parts of interface strengthening material and 50-80 parts of water. The nanometer channel sealing adsorption material is composed of silica sand and nanometer liquid silicon, and the mass ratio of the silica sand to the nanometer liquid silicon is 1: (3-4).

[0008] The selective temporary plugging material is composed of a polyacrylamide quaternary copolymer, a urea-formaldehyde resin emulsion and a composite surfactant, and the mass ratio of the three is 3: (2-2.5): (3-3.5). The urea-formaldehyde resin emulsion is a urea-formaldehyde resin with a solid content of 40%-50%.

[0009] The interface reinforcement material consists of hexametaphosphate and anhydrous sodium silicate, and the mass ratio of the hexametaphosphate to the anhydrous sodium silicate is 1:(1-1.5).

[0010] The silica sand density range is 2.4-2.65g / cm 3 , particle size range is 45-85 nm, silicon dioxide mass content is greater than 95%, and the nano-liquid silicon density range is 1.1-1.45 g / cm 3 , particle size range is 20-50nm, and silica mass content is 35-45%.

[0011] The molecular weight of the acrylamide-based quaternary copolymer is 5-8 million, the solid content of the urea-formaldehyde resin emulsion is 70%, and the particle size is 200-220 nm.

[0012] The composite surfactant is composed of one or more of alkylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, glyceryl monostearate, fatty acid glyceride, fatty acid sorbitan, and polysorbate.

[0013] The density of the pre-liquid system is 1.15-1.45 g / cm 3 , temperature resistance above 150°C, plastic viscosity <0.4Pa•s, and interface bonding strength greater than 2.5MPa.

[0014] A method for preparing a pre-fluid system for cementing and water plugging comprises the following steps: Step 1) uniformly mixing the formulated amount of nano-liquid silicon, the selective temporary plugging material and water to obtain a mixed solution; Step 2) dry-mixing the formulated amount of silica sand and the interface reinforcement material into a solid phase mixture; Step 3) adding the solid phase mixture into the mixed solution at a low speed of 4000±200 r / min, and then continuously stirring at a high speed of 8000±200 r / min to obtain.

[0015] The beneficial effects of the present invention are: The pre-fluid system for cementing and water plugging provided by the present invention is mainly composed of nano-sealing adsorption materials and selective temporary plugging materials, and is compounded with well wall interface strengthening materials to form a pre-fluid system for pre-sealing water layers before cementing. The selective temporary plugging materials of this system are used to plug and fill long open hole and large sections of water layers. The nano-plugging materials remaining near the well wall are highly active and can effectively participate in cement hydration by utilizing the volcanic ash effect with cement, shortening the gelling transition time of cement stone at the interface near the well wall. The hydrated calcium silicate formed with cement has weak sensitivity and is suitable for various formation fluids. In combination with the interface strengthening materials, it can effectively provide the interface bonding strength of the water layer section, improve the interface plugging quality of the water layer in the oil field, and effectively reduce the interface sealing failure and water layer cement sealing quality problems caused by the intrusion of flowing water in the water layer and ion exchange. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the interface bonding strength test principle of an embodiment of the present invention. DETAILED DESCRIPTION

[0017] The following describes the implementation of the present invention through specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0018] The exemplary embodiments of the present invention are now described with reference to the accompanying drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. These embodiments are provided to disclose the present invention in detail and completely and to fully convey the scope of the present invention to those skilled in the art. The terms used in the exemplary embodiments shown in the accompanying drawings are not intended to limit the present invention.

[0019] Unless otherwise specified, the terms (including technical terms) used herein have the commonly understood meanings to those skilled in the art. In addition, it is understood that the terms defined in commonly used dictionaries should be understood to have the same meanings as those in the context of the relevant fields, and should not be understood as idealized or overly formal meanings.

[0020] Example 1 The present embodiment provides a pre-fluid system for cementing and water plugging, comprising the following components in parts by weight: 10-30 parts of nano-channeling blocking adsorption material, 8-20 parts of selective temporary plugging material, 2-5 parts of interface enhancement material, and 50-80 parts of water. Among them, the nano-sealing adsorption material is composed of silica sand and nano-liquid silicon, and the mass ratio of silica sand to nano-liquid silicon is 1: (3-4). The adsorption material mixed with nano-liquid silicon and silica sand has strong water absorption and strong thixotropic properties, can effectively block the water-producing layer, and the retained part of the well wall can participate in the hydration of the cement interface.

[0021] The selective temporary plugging material is composed of a polyacrylamide quaternary copolymer, a urea-formaldehyde resin emulsion and a composite surfactant, the mass ratio of the three being 3: (2-2.5): (3-3.5), and the urea-formaldehyde resin emulsion is a urea-formaldehyde resin with a solid content of 40%-50%. The selective water plugging material, in combination with the nano-sealing adsorption material, can selectively plug water without plugging oil.

[0022] The interface reinforcement material is composed of hexametaphosphate and anhydrous sodium silicate, wherein the mass ratio of the hexametaphosphate to the anhydrous sodium silicate is 1:(1-1.5). Both the hexametaphosphate and the anhydrous sodium silicate have an early strength effect and participate in the later stage of oil well cement hydration.

[0023] The pre-fluid system for cementing and water plugging provided by the present invention is mainly composed of nano-sealing adsorption materials and selective temporary plugging materials, and is compounded with well wall interface strengthening materials to form a pre-fluid system for pre-sealing water layers before cementing. The selective temporary plugging materials of this system are used to plug and fill long open hole and large sections of water layers. The nano-plugging materials remaining near the well wall are highly active and can effectively participate in cement hydration by utilizing the volcanic ash effect with cement, shortening the gelling transition time of cement stone at the interface near the well wall. The hydrated calcium silicate formed with cement has weak sensitivity and is suitable for various formation fluids. In combination with the interface strengthening materials, it can effectively provide the interface bonding strength of the water layer section, improve the interface plugging quality of the water layer in the oil field, and effectively reduce the interface sealing failure and water layer cement sealing quality problems caused by the intrusion of flowing water in the water layer and ion exchange.

[0024] Example 2 Based on Example 1, this example provides a pre-fluid system for cementing and water plugging, comprising the following components in parts by weight: 20 parts of nano-blocking adsorption material, 8 parts of selective temporary plugging material, 2 parts of interface enhancement material, and 70 parts of water. Preparation process: Step 1) uniformly mixing the formulated amount of nano-liquid silicon, the selective temporary plugging material and water to obtain a mixed solution; Step 2) dry-mixing the formulated amount of silica sand and the interface reinforcement material into a solid phase mixture; Step 3) Add the solid phase mixture to the mixed solution at a low speed of 4000±200 r / min within 15 seconds, and then continue stirring at a high speed of 8000±200 r / min for 35 seconds to obtain.

[0025] In this embodiment, the nano-sealing adsorption material is composed of silica sand and nano-liquid silicon in a mass ratio of 1:4, 16 parts of nano-liquid silicon and 4 parts of silica sand; the selective temporary plugging material is composed of a polyacrylamide tetrapolymer, urea-formaldehyde resin emulsion and a composite surfactant in a mass ratio of 3:2:3, wherein the surfactant is alkylphenol polyoxyethylene ether; the interface strengthening material is composed of hexametaphosphate and anhydrous sodium silicate in a mass ratio of 1:1.

[0026] The pre-fluid system for cementing and plugging water of the present invention is compounded with a selective temporary plugging material and a nanometer channel blocking adsorption material, and comprehensively uses the particle grading theory and the plugging function of the nanometer emulsion to improve the pre-plugging effect of the water layer and selectively plug the water layer without plugging the oil layer channel.

[0027] Example 3 Based on Example 1, this example provides a pre-fluid system for cementing and water plugging, comprising the following components in parts by weight: 27 parts of nano-blocking adsorption material, 10 parts of selective temporary plugging material, 3 parts of interface enhancement material, and 60 parts of water. The preparation process is the same as Example 2.

[0028] In this embodiment, the nano-sealing adsorption material is composed of silica sand and nano-liquid silicon in a mass ratio of 1:3, 20.25 parts of nano-liquid silicon and 6.75 parts of silica sand; the selective temporary plugging material is composed of a polyacrylamide tetrapolymer, a urea-formaldehyde resin emulsion and a composite surfactant in a mass ratio of 3:2.5:3.5, wherein the surfactant is alkylphenol polyoxyethylene ether and sodium dodecylbenzene sulfonate in a mass ratio of 1:2; the interface strengthening material is composed of hexametaphosphate and anhydrous sodium silicate in a mass ratio of 1:1.5.

[0029] Example 4 Based on Example 1, this example provides a pre-fluid system for cementing and water plugging, comprising the following components in parts by weight: 30 parts of nano-blocking adsorption material, 18 parts of selective temporary plugging material, 2 parts of interface enhancement material, and 50 parts of water. The preparation process is the same as Example 2.

[0030] In this embodiment, the nano-sealing adsorption material is composed of silica sand and nano-liquid silicon, with 4 parts of nano-liquid silicon and 6 parts of silica sand; the selective temporary plugging material is composed of a polyacrylamide tetrapolymer, a urea-formaldehyde resin emulsion and a composite surfactant in a mass ratio of 3:2:3, wherein the surfactant is a mixture of monostearate glyceryl, fatty acid glyceride, fatty acid sorbitan and polysorbate in a mass ratio of 1:2:3:1; the interface strengthening material is composed of hexametaphosphate and anhydrous sodium silicate in a mass ratio of 1:1.

[0031] The on-site use method of the pre-fluid system for cementing and water plugging is to pump the pre-fluid system for water plugging into the cementing annulus before cementing construction to perform selective water layer pre-plugging construction, thereby reducing water layer sealing quality problems caused by water layer intrusion and ion exchange and ensuring the sealing quality of the water layer interface.

[0032] In order to further illustrate the effect of the present invention, the pre-fluid system for cementing and water plugging prepared in Examples 2-4 was subjected to an interface bonding strength evaluation test and a density test, and the existing pre-fluid system was used as a comparative example for comparison, wherein the comparative example consisted of the following substances in the following mass percentages: 5% surfactant, 2% KCl, and the rest water.

[0033] 1) Interface bonding strength evaluation test: In order to evaluate the performance of the pre-fluid system for cementing and water plugging, artificial simulated cores are taken to simulate the bonding condition between the formation and cement stone after pre-plugging. The tested bonding strength is the bonding strength between the cement stone and the formation core containing the pre-plugging material. The simulation effect is more realistic. The test principle is as follows: Figure 1 shown.

[0034] The testing process is as follows: The core is immersed in a strength mold with a hollow support installed, placed in a high-temperature curing box for mud curing for 24 hours, a filter cake is formed on the surface of the core, and then placed in a pressurized curing kettle for pressurized curing for 2 hours with a pre-fluid system for cementing and plugging water, and then cement slurry is poured in, and the curing test mold and cement slurry are cured in a high-temperature curing box at 70°C for 24 hours to form a cement ring between the cement stone and the formation core containing the pre-plugging material, and then a pressure tester is used to test the bonding strength between the cement stone and the formation core containing the pre-plugging material. For details, see patent CN105092465B.

[0035] Bond strength Among them, F 剪切力 is the pressure value when the cement and the outer wall of the core are loose, in N; D and H are the diameter and height of the core, in mm.

[0036] The test results are shown in Table 1.

[0037] Among them, the pressurized curing kettle uses the HTD7370 model high-temperature curing kettle of the Institute of Applied Technology of Shenyang Aerospace University, the high-temperature curing box uses the OWC-118 model high-temperature curing box of the Institute of Applied Technology of Shenyang Aerospace University, and the pressure testing machine is the WHY-300 / 10 model microcomputer fully automatic controlled pressure testing machine of Shanghai Hualong Testing Instrument Co., Ltd.

[0038] 2) Density test The measurement was performed using a digital liquid density meter, which was a YMS1-5 digital density meter produced by Qingdao Haitongda Special Instrument Factory.

[0039] Table 1 Performance test results The existing cementing pre-fluid is of flushing type, which is for interface cleaning and wetting, and does not have water blocking performance in water layer. This can also be explained from the experimental results in Table 1. The bonding strength of the comparative example is low and it is impossible to pre-block the water layer.

[0040] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. All designs that are the same or similar to the present invention fall within the protection scope of the present invention.

Claims

1. A pre-fluid system for cementing and water plugging, characterized in that: The invention comprises the following components in parts by weight: 10-30 parts of nanometer channel blocking and adsorption material, 8-20 parts of selective temporary blocking material, 2-5 parts of interface strengthening material and 50-80 parts of water.

2. A pre-fluid system for cementing and water plugging according to claim 1, characterized in that: The nanometer channel sealing adsorption material is composed of silica sand and nanometer liquid silicon, and the mass ratio of the silica sand to the nanometer liquid silicon is 1: (3-4).

3. A pre-fluid system for cementing and water plugging according to claim 1, characterized in that: The selective temporary plugging material is composed of a polyacrylamide-based quaternary copolymer, a urea-formaldehyde resin emulsion and a composite surfactant, and the mass ratio of the three is 3: (2-2.5): (3-3.5). The urea-formaldehyde resin emulsion is a urea-formaldehyde resin with a solid content of 40%-50%.

4. A pre-fluid system for cementing and water plugging according to claim 1, characterized in that: The interface reinforcement material consists of hexametaphosphate and anhydrous sodium silicate, and the mass ratio of the hexametaphosphate to the anhydrous sodium silicate is 1:(1-1.5).

5. A pre-fluid system for cementing and water plugging according to claim 2, characterized in that: The silica sand density range is 2.4-2.65g / cm 3 , particle size range is 45-85 nm, silicon dioxide mass content is greater than 95%, and the nano-liquid silicon density range is 1.1-1.45 g / cm 3 , particle size range is 20-50nm, and silica mass content is 35-45%.

6. A pre-fluid system for cementing and water plugging according to claim 2, characterized in that: The molecular weight of the acrylamide-based quaternary copolymer is 5-8 million, the solid content of the urea-formaldehyde resin emulsion is 70%, and the particle size is 200-220 nm.

7. A pre-fluid system for cementing and water plugging according to claim 3, characterized in that: The composite surfactant is composed of one or more of alkylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, glyceryl monostearate, fatty acid glyceride, fatty acid sorbitan, and polysorbate.

8. A pre-fluid system for cementing and water plugging according to any one of claims 1 to 7, characterized in that: The density of the pre-liquid system is 1.15-1.45 g / cm 3 , temperature resistance above 150°C, plastic viscosity <0.4Pa•s, and interface bonding strength greater than 2.5MPa.

9. The method for preparing a pre-fluid system for cementing and water plugging according to claim 2, characterized in that: The following steps are involved: Step 1) uniformly mixing the formulated amount of nano-liquid silicon, the selective temporary plugging material and water to obtain a mixed solution; Step 2) dry-mixing the formulated amount of silica sand and the interface reinforcement material into a solid phase mixture; Step 3) adding the solid phase mixture into the mixed solution at a low speed of 4000±200 r / min, and then continuously stirring at a high speed of 8000±200 r / min to obtain.

Citation Information

Patent Citations

  • A device and method for testing the cement bond strength of well cement.

    CN105092465B

  • Interface enhanced prepad fluid for well cementation in oil field as well as preparation method and application of interface enhanced prepad fluid

    CN114605975A

  • Mud cake curing and cementing pre-liquid system and preparation method thereof

    CN106928949A

  • Composite gel well killing rubber plug capable of rapidly gelatinizing and weighting at high temperature and preparation method thereof

    CN111410943A

  • High-temperature-resistant elastic and tough anti-channeling cement slurry system and preparation method thereof

    CN112979221A